(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2025)
Freedom of expression constitutes both an individual right and an institutional guarantee of democracy, political pluralism, and the rule of law. It faces today classic attacks such as censorship or the persecution of journalists. At the same time, new challenges have emerged in relation to content that violates the rights of others (hate speech) or the functioning of democracy (fake news). Similarly, the State’s obligations to guarantee, control and protect are confronted with challenges such as new actors (companies’ abilities and liability over the control of digital networks’ contents), or the automation of content production and oversight processes (artificial intelligence). This work enhances the role and responsibility of the State in terms of classic attribution of responsibility, which was already highlighted in the first matter on freedom of expression before the Inter–American Court, as described by its then President, Judge Cançado Trindade.